Resolving ethical dilemma in technology enhanced education through smart mobile devices - Muhammad, AbdulHafeez; Ahamd, Farooq; Shah, Asadullah (Arab Open University, 2015)
With the recent development of Information and Communication Technologies (ICT) in all sectors specially in education, technology Enhanced Education (TEE) has become an evolutionary mode in educational institutes by choice and demand. Technology, especially Smart Mobile Device (SMD) has lot of potential to enrich and accelerate the deepen skills of students, to engage and motivate them in studies for making tomorrow's professionals. Moreover it has helped academic institutions in education process. On the other hand academic dishonesty and cheating has become an ethical dilemma in these institutions using these technologies. It is a quite concern that graduates producing through TEE are like machines, lacking of ethical and moral values because of this dilemma. To resolve this, authors have proposed to involve traditional players of character development of individual in Learning Management Systems 9LMS) of academic institutions. The paper aims to promote this concept by providing a model to help academic institutions, educationist and researchers to use technology in constructive way for controlling academic dishonesty and transmitting ethical values in educational system.